Zainteresowany w postępowaniu w sprawach z zakresu ubezpieczeń społecznych — założenia konstrukcyjne na tle ogólnych założeń postępowania cywilnego - Rylski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
In the special proceedings in cases within the subject matter and scope of social insurance as aparty to proceedings is also treated the interested person. According to Polish Code of Civil Proicedure interested person is aperson whose rights and obligations are affected by the outcome of acase. If the interested person does not participate in acase, the court shall notify them of the proceedings. The interested person may join the case within two weeks as of serving the notice. This regulation is very similar to the “principle of multilateral participation of interested persons” adopted in non-contentious proceedings. This article aims to provide ageneral overview at the concept and notion of principle of multilateral participation in the special proceedings in cases within the subject matter and scope of social insurance. This special proceedings, although is apart of contentious proceedings, was not based on the two — party principle, traditionally present in the trial. As it seems this is aresult of subject matter relationships which are recognized in these proceedings. The author emphasises that this is one of the most important premises of introducing so called principle of multilateral participation to different trial-mode proceedings.
Keywords: ubezpieczenie społeczne; zainteresowana osoba; postępowanie cywilne